2014
DOI: 10.1016/j.celrep.2014.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Disease Modeling and Phenotypic Drug Screening for Diabetic Cardiomyopathy using Human Induced Pluripotent Stem Cells

Abstract: Diabetic cardiomyopathy is a complication of type 2 diabetes, with known contributions of lifestyle and genetics. We develop environmentally and genetically driven in vitro models of the condition using human-induced-pluripotent-stem-cell-derived cardiomyocytes. First, we mimic diabetic clinical chemistry to induce a phenotypic surrogate of diabetic cardiomyopathy, observing structural and functional disarray. Next, we consider genetic effects by deriving cardiomyocytes from two diabetic patients with variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
206
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(216 citation statements)
references
References 25 publications
9
206
0
1
Order By: Relevance
“…Induced type II diabetic cardiomyopathy was also modeled in hiPSC-CMs following prolonged exposure to "diabetic milieu" consisting of a combination of glucose, ET-1, and cortisol (61). Gene set enrichment analysis (GSEA) using RNA-sequencing gene expression data showed significant upregulation in metabolic genes involved in the tricarboxylic acid (TCA) cycle (e.g., PDK1), mitochondrial electron transport chain (e.g., CYCS), glucose metabolism (e.g., ENO2), cell adhesion (e.g., integrins), and extracellular matrix deposition (e.g., collagens), whereas downregulation was observed in genes related to protein synthesis and the cellular response to dysfunctional protein production (e.g., ATF4 and CHOP10).…”
Section: Secondary Cardiomyopathymentioning
confidence: 99%
“…Induced type II diabetic cardiomyopathy was also modeled in hiPSC-CMs following prolonged exposure to "diabetic milieu" consisting of a combination of glucose, ET-1, and cortisol (61). Gene set enrichment analysis (GSEA) using RNA-sequencing gene expression data showed significant upregulation in metabolic genes involved in the tricarboxylic acid (TCA) cycle (e.g., PDK1), mitochondrial electron transport chain (e.g., CYCS), glucose metabolism (e.g., ENO2), cell adhesion (e.g., integrins), and extracellular matrix deposition (e.g., collagens), whereas downregulation was observed in genes related to protein synthesis and the cellular response to dysfunctional protein production (e.g., ATF4 and CHOP10).…”
Section: Secondary Cardiomyopathymentioning
confidence: 99%
“…The ambition to implement hiPSC‐CMs in precision medicine partially relies on their ability to predict patients’ response to administered drugs. Recent studies provide optimism in this direction 15, 63, 74, although additional consent and focussed investigations will be needed to determine the extent to which individual variability can be distinguished in the hiPSC‐CMs, including mild or severe, acute, early or late responses. Of note, all studies so far have been based on a small number of patients per group and were conducted retrospectively.…”
Section: Future Challengesmentioning
confidence: 99%
“…iPS cells can also serve as a valuable resource in the absence of cellular or animal models mimicking human diseases. Various disease-specific human iPS cells have been generated including type 1 and type 2 diabetes, complex diseases such as diabetic cardiomyopathy, and several monogenic diseases which enabled investigators to explore human diseases in petri dishes [4244]. A recent study from our group showed feasibility of using human iPS cells in modeling diabetic complications.…”
Section: The Use Of Stem Cell-derived Pancreatic Cells In Investigatimentioning
confidence: 99%